Effect of Beta 3 Adrenoreceptor Modulation on Patency of the Ductus Arteriosus - Alessandro Pini; Camilla Fazi; Patrizia Nardini; Maura Calvani; Sergio Fabbri; Alessandro Guerrini; Giulia Forni; Giancarlo La Marca; Arianna Carolina Rosa; Luca Filippi (Cells, 2020)
β3-adrenoreceptor (β3-AR), a G-protein coupled receptor, has peculiar regulatory properties in response to oxygen and widespread localization. β3-AR is expressed in the most frequent neoplasms, also occurring in pregnant women, and its blockade reduces tumor growth, indicating β3-AR-blockers as a promising alternative to antineoplastic drugs during pregnancy. However, β3-AR involvement in prenatal morphogenesis and the consequences of its blockade for the fetus remain unknown. In this study, after the demonstrated expression of β3-AR in endothelial and smooth muscle cells of ductus arteriosus (DA), C57BL/6 pregnant mice were acutely treated at 18.5 of gestational day (GD) with indomethacin or with the selective β3-AR antagonist SR59230A, or chronically exposed to SR59230A from 15.5 to 18.5 GD. Six hours after the last treatment, fetuses were collected. Furthermore, newborn mice were treated straight after birth with BRL37344, a β3-AR agonist, and sacrificed after 7 h. SR59230A, at the doses demonstrated effective in reducing cancer progression (10 and 20 mg/kg) in acute and chronic mode, did not induce fetal DA constriction and did not impair the DA ability to close after birth, whereas at the highest dose (40 mg/kg), it was shown to cause DA constriction and preterm-delivery. BRL37344 administered immediately after birth did not alter the physiological DA closure.